Otimização de escala de tratamento de quimioterapia: aplicação ao Hospital das Clínicas da UFMG - Nana Flora Elias Pompeu (2018)
When working with offline scheduling, daily template for online patient scheduling is a useful tool. Therefore, this work focuses on establishing an efficient scheduling template for chemotherapy sections in the ambulatory Borges da Costa. The sessions differ from each other regarding the type of drug administered and the infusion time required. Historical data indicates the frequency in which these different types of treatments take place daily and this is the basis for the determination of the daily demand for the treatments. The limited clinic resources are the chairs, the total daily working hours, the drugs handling capacity and the nurses workload. In this scenario it is considered different acuity levels for the patients. The analysis in the present document concentrates on how to increase the total numbers of patients while maintaining the frequency of occurrence between the different possible sessions types. The results show that the limited resource of this environment is the pharmacist capacity and therefore this should be the address to an eventual investment in the ambulatory. Given the modelled scenario the proposed scheduling template increases in 70% the ambulatory patient handling capacity